Visual Mapping of Operating Theater Team Dynamics and Communication for Reflexive Feedback and Surgical Practice Optimization - Surya Surendran, MA; Candice Bonaconsa, MSc; Vrinda Nampoothiri, PharmD; Oluchi Mbamalu, PhD; Anu George, PGDip; Swetha Mallick, MCh; Sudheer OV, MCh; Alison Holmes, MD; Marc Mendelson, PhD; Sanjeev Singh, PhD; Gabriel Birgand, PhD; Esmita Charani, PhD (Annals of Surgery Open)
Background:. Effective operating theater (OT) communication and teamwork are essential to optimal surgical outcomes. We mapped the OT team dynamics and infection control practices using visual methods to guide reflexive feedback and optimize perioperative practices. Methods:. Data were gathered from adult gastrointestinal surgical teams at a tertiary hospital in India using observations, sociograms (communication mapping tool), and focus group discussions (FGDs). Our methods aimed to map team communication, roles and responsibilities in infection-related practices, and door openings. Qualitative data were thematically analyzed. Quantitative data were analyzed using descriptive statistics. Results:. Data were gathered from 10 surgical procedures (over 51 hours) using 16 sociograms, 15 traffic flow maps, and 3 FGDs. Senior surgeons directly influence team hierarchies, dynamics, and communication. While the surgeons, anesthetic residents, and technicians lead most tasks during procedures, the scrub nurse acts as a mediator coordinating activity among role players across hierarchies. Failing to provide the scrub nurse with complete details of the planned surgery leads to multiple door openings to fetch equipment and disposables. Traffic flow observed in 15-minute intervals corresponds to a mean frequency of 56 door openings per hour (min: 16; max: 108), with implications for infection control. Implementing the World Health Organization surgical safety checklist was inconsistent across pathways and does not match reported compliance data. Conclusions:. Human factors research is important in optimizing surgical teamwork. Using visual methods to provide feedback to perioperative teams on their communication patterns and behaviors, provided an opportunity for contextualized enhancement of infection prevention and control practices.